Integration of Design Approach and Digital Technology in Preserving Architectural Heritage in Indonesia - Mutaqi, Ahmad Saifudin; Ardiyanto, Antonius (CV. Gio Architect, 2025)
Digital design and technology are increasingly playing an important role in the preservation of cultural heritage in Indonesia, along with the ongoing digital transformation in various cultural institutions. This phenomenon presents challenges in selecting the right technology and opportunities to create more inclusive, immersive, and contextual digital experiences. The main issue raised is the absence of a systematic approach in the application of digital technology that is in accordance with the characteristics and needs of each type of heritage, such as colonial buildings, traditional buildings, and temple buildings. This study aims to examine the contribution of design approaches in developing digital solutions for conservation and evaluate the suitability of various digital technology platforms in the context of the three categories of architectural heritage. The method used is a literature study with a comparative analysis of the application of digital technology in a number of cultural heritage sites in Indonesia. The results of the study show that each category of building has different technical, narrative, and visual needs, thus requiring a specific and targeted technological approach. A design approach integrated with software engineering principles has been proven to strengthen the effectiveness of conservation and expand the reach of education and public appreciation of cultural heritage through digital media.